IBU DAN ANAK DALAM KARYA GRAFIS STENCIL PRINT - Dra. Ernis, M.Pd., Febby Anggraini, Yofita Sandra, S.Pd., M.Pd., (Jurusan Seni Rupa FBS UNP Padang, 2017)
The purpose of making this final works was to express about the mother’s love and a child, that becoming inspiration in this graphic’s art work with stencil print technique. The method of creating art works used five preparation’s stage. they were elaboration, synthesis, concepts’ realization and completion also the last stage was exhibition of graphic works. The conclusion talked a mother’s love to a child is very necessary for child’s growing.Keywords: Mother, Child, Idea, Graphic